2008
DOI: 10.1002/pbc.21547
|View full text |Cite
|
Sign up to set email alerts
|

Wilms tumour in Sudan

Abstract: The poor outlook is related to several factors. Delayed presentation, poor awareness of treatment options, lack of finances, no provision of food, lodging and transport, absence of paediatric trained staff are the obstacles to better outcomes. Empowering parents with information, giving chemotherapy prior to nephrectomy, training staff and establishing links with a tertiary cancer centre in the developed world are some of the options to improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 16 publications
8
85
1
Order By: Relevance
“…The interval between the end of preoperative chemotherapy and surgery, and between surgery and the start of postoperative therapy was not respected because the surgeon was not available or because the pathology report was not available. This situation, which is unknown or rare in developed countries, has to be compared to those described in other African countries which have, to various degrees, similar socio-economic problems [12,13]. The absence of radiotherapy for selected patients less than 3 years of age, with a small stage III tumor, initially treated by surgery, did not seem to influence the prognosis for this tiny minority [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval between the end of preoperative chemotherapy and surgery, and between surgery and the start of postoperative therapy was not respected because the surgeon was not available or because the pathology report was not available. This situation, which is unknown or rare in developed countries, has to be compared to those described in other African countries which have, to various degrees, similar socio-economic problems [12,13]. The absence of radiotherapy for selected patients less than 3 years of age, with a small stage III tumor, initially treated by surgery, did not seem to influence the prognosis for this tiny minority [17].…”
Section: Discussionmentioning
confidence: 99%
“…The SIOP studies demonstrated the value of preoperative chemotherapy [3] to limit the risk of tumor rupture during surgery, to increase the percentage of stage I tumors requiring less aggressive treatments and to limit complications associated with surgery [9]. In Africa, the results of such treatment management are fragmentary [10][11][12][13] or are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Survival in low income countries is much lower than in high income countries with reported survival in low income settings in sub-Saharan Africa ranging from 11% to 50% [3][4][5][6][7]. Known challenges are late presentation with advanced disease, malnutrition, failure to complete treatment and poorer facilities both for the specific cancer treatment and also for supportive care [4,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Known challenges are late presentation with advanced disease, malnutrition, failure to complete treatment and poorer facilities both for the specific cancer treatment and also for supportive care [4,5,8]. Capacity building, earlier presentation, social support, improved supportive care and a treatment guideline adapted to local circumstances are key to improving results [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Building Sustainable Capacity for Disease Diagnosis in Sub-Saharan Africa: Case Studies of Cooperation in Diagnostic Pathology 257 good quality research, and training programs (Dessein et al 1999;Mohamed-Ali et al 1999;Abel et al 2000;Pascal et al 2000;Henri et al 2002;Chevillard et al 2003;Dessein et al 2004;Alsheikh et al 2006;Awadelkarim et al 2007;Abuidris et al 2008a;Abuidris et al 2008b;Abuidris et al 2008c;Awadelkarim et al 2008;Dessein et al 2009;Faggad et al 2009a;Faggad et al 2009b;Rahoud et al 2009;Tofanelli et al 2009;Awadelkarim et al 2010a;Awadelkarim et al 2010b;Elgaili et al 2010;Elwali et al 2010;Ali et al 2011;Awadelkarim et al 2011). Its Nuclear Medicine, Oncology, Molecular Biology, Medical Physics and Engineering, Diagnostic Imaging and Medical Laboratories Departments make NCI-UG the only cancer institute outside the capital Khartoum (Figure 9).…”
Section: Wwwintechopencommentioning
confidence: 99%